Understanding the sales process: selling in the 21st century - Macdivitt, Harry (Henry Stewart Talks, 2010)
There are many sales processes in use today, Most share common themes of prospecting, qualifying, needs analysis, presentation, negotiation and follow up, These classical approaches have served sales people well over the years and are still valid, The job of selling is changing and with this change, the role and skills of salespeople are also changing, Selling is now a much more strategic function, The modern sales person operates in a more complex, more competitive and more knowledge based environment, Modern sales professionals are no longer "box shifters" and are now accomplished "merchants of value", What value means and how to create value for clients and customers is the factor that differentiates the effective modern sales professional from his peers